BORON. PROPERTIES AND APPLICATION IN NUCLEAR ENERGY - V. A. Palekha; A. A. Getman (Литьë и металлургия, 2017)
Boron is one of the available chemical elements actively influencing the properties of the alloys. The main use of boron is in the alloys of the control rods of nuclear reactors to stop or slow down the fission reaction.